2006
DOI: 10.1042/bst20060223
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of acetyl-CoA carboxylase

Abstract: Acetyl-CoA carboxylase (ACC) catalyses the formation of malonyl-CoA, an essential substrate for fatty acid synthesis in lipogenic tissues and a key regulatory molecule in muscle, brain and other tissues. ACC contributes importantly to the overall control of energy metabolism and has provided an important model to explore mechanisms of enzyme control and hormone action. Mammalian ACCs are multifunctional dimeric proteins (530-560 kDa) with the potential to further polymerize and engage in multiprotein complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(66 citation statements)
references
References 65 publications
2
62
0
2
Order By: Relevance
“…ACC, the rate-limiting enzyme in de novo fatty acid synthesis [35], is enriched in lipogenic tissues such as adipose and the lactating mammary gland [36], [37]. Previous studies have reported decreased expression and activity of lipogenic enzymes, including ACC, in lactating mammary glands related HF feeding and/or obesity [11], [15], [38].…”
Section: Resultsmentioning
confidence: 99%
“…ACC, the rate-limiting enzyme in de novo fatty acid synthesis [35], is enriched in lipogenic tissues such as adipose and the lactating mammary gland [36], [37]. Previous studies have reported decreased expression and activity of lipogenic enzymes, including ACC, in lactating mammary glands related HF feeding and/or obesity [11], [15], [38].…”
Section: Resultsmentioning
confidence: 99%
“…Citrate is converted to acetyl-CoA, by the action of adenosine triphosphate citrate lyase (ACL), which is the first step of endogenous fatty acid synthesis (Figure 1). Furthermore, citrate is an allosteric activator of cytoplasmic acetyl-CoA carboxylase (ACC), whose action is to convert acetyl-CoA to malonyl-CoA, thus initiating de novo lipogenesis (25; 26). Malonyl-CoA, is the primary carbon source utilized for endogenous fatty acid synthesis (27).…”
Section: Hepatic De Novo Lipogenesismentioning
confidence: 99%
“…1a) (Bianchi et al 1990; Tanabe et al 1975; Tong 2013). Biotin is covalently attached to lysine within BCCP domain through posttranslational modification, and several serine residues are phosphorylated by protein kinases (Beaty and Lane 1983a; Brownsey et al 2006; Ha et al 1994; Meredith and Lane 1978). We deleted the N-terminal 148 hydrophobic amino acids to enhance the solubility of heterologous protein, which retains core functional modules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Acetyl-CoA carboxylases (ACCs) are biotin-dependent enzymes catalyzing the production of malonyl-CoA from acetyl-CoA, a critical metabolic intermediate in lipid metabolism (Brownsey et al 2006; Kim 1997; Saggerson 2008; Tong 2013; Wakil and Abu-Elheiga 2009). Two different isoforms of ACC, ACC1 and ACC2, partake in lipid metabolism in humans and mammals (Abu-Elheiga et al 1995, 1997; Ha et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation